2017
DOI: 10.1080/07448481.2017.1322090
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the mental health service utilization decisions of university undergraduates: A discrete choice conjoint experiment

Abstract: E-Mental Health options could engage students who may not wait for standard services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
1
25
1
1
Order By: Relevance
“…In the current study, half of participants reported that user-led peer support should happen more at their university, with a third reporting that they would access peer support but most unsure if they would access it. This supports previous research demonstrating a desire for peer support services (Cunningham et al 2017;Shaw 2014) although the number of unsure participants indicates that they may benefit from further information about peer support. The main reasons participants wanted peer support was to support recovery and meet new people.…”
Section: Attitudes Towards Peer Supportsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, half of participants reported that user-led peer support should happen more at their university, with a third reporting that they would access peer support but most unsure if they would access it. This supports previous research demonstrating a desire for peer support services (Cunningham et al 2017;Shaw 2014) although the number of unsure participants indicates that they may benefit from further information about peer support. The main reasons participants wanted peer support was to support recovery and meet new people.…”
Section: Attitudes Towards Peer Supportsupporting
confidence: 87%
“…Three-quarters of participants reported that they were more confident talking about their mental health post-intervention, noting the sessions helped them improve their ability to take care of their own mental health (Byrom 2018). Further, Cunningham et al (2017) found that when students picked between hypothetical mental health services, 40% reported that they would prefer to talk to peers who had similar experiences over professional services. Peer support may thus offer a useful and desired alternative to professional services.…”
mentioning
confidence: 99%
“…A study of university undergraduates in a Canadian university found three groups of student preferences for services: a group (45.5%) that preferred university-based psychological or psychiatric professional services, a group that preferred alternative services (39.3%) such as peer counseling or e-mental health options, and a small hesitant group (15.2%) that would prefer not to seek help even though clearly distressed. 40 Interestingly, in our study, the proportion of students with probable 12-month disorders who have received services is lower than the proportion of students who say they would seek services if they had a mental health problem. This may be due to students not recognizing that they have a problem, not knowing where to find services, the lack of services or barriers to service use.…”
Section: Treatment Possibilities For University Studentscontrasting
confidence: 65%
“…Conjoint methods sharpen the focus on “what it is about treatment” that drives preferences and provides specific guideposts for how to design packages of treatment that are patient-centered. A number of studies covered depression and psychosocial support [ 15 , 28 – 33 , 35 , 37 – 40 , 42 , 43 , 53 , 54 , 57 – 59 ] from the premise that theoretical assimilation of intervention or treatment preference characteristics might vary from real life choices and concerns. A DCE is a quantitative tool that measures the weight of different factors that affect a decision.…”
Section: Discussionmentioning
confidence: 99%